Business Finance Needs and Decision-Making Factors - Ludmila Cobzari; Eugenia BUSMACHIU; Svetlana GHERJAVCA (ACROSS)
Ensuring the efficient management of the company’s activity and obtaining the expected results entail the elaboration of a financial policy oriented towards attracting own and borrowed financial resources from various sources. The financial policy aims to ensure a necessary level of self-financing. The need for financing, but also the real possibilities for attracting financial resources are not the same for all the entities, being conditioned by a series of factors. The study of the factors of influence and their administration ensures the determination of the financial cycle and guarantees a financial balance between the needs and the sources of financing of the enterprise.